Capacidade funcional em cavalos de salto suplementados com linhaça - Oliveira, K. [UNESP]; Heinrichs, R. [UNESP]; Costa, C. [UNESP]; Millen, D.d. [UNESP]; Meirelles, P.r.l. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2014)
The objective of this study was to evaluate the supplementation of linseed as an omega-3 fatty acid supplier on the functional capacity of jumping horses. 6 horses disposed in two 3 x 3 balanced Latin squares were used. The treatments consisted of increasing levels of linseed mixed with flour and linseed oil in a ratio of 75:25, respectively, resulting in 0g (control), 60g and 120g on a daily basis per horse. The horses were supplemented for 30 days. Physical activity was jumping at riding class level. The functional parameters measured were lameness index, stride length and joint metacarpophalangeal (MCP) biometry (circumference and flexion angle). A significant linseed supplementation effect for doses of 60 and 120g was observed on the lameness index. Feeding 120g of linseed increased stride length while trotting (P<0.05). An increment of 0.5cm on MCP circumference was found in horses that received the control diet when compared to those horses that consumed 120g of linseed. Thus, supplementation of jumping horses with 120g/day of linseed promoted greater stride length at a trot and reduced swelling in the metacarpophalangeal joint, improving their functional capabilities.

Objetivou-se avaliar a suplementação com linhaça, como fonte do ácido graxo ômega-3, sobre a capacidade funcional de cavalos de salto. Foram utilizados seis equinos distribuídos em dois quadrados latinos 3x3 balanceados. Os grupos experimentais consistiram em níveis crescentes de linhaça (na forma de farinha e óleo de linhaça na proporção de 75:25, respectivamente), resultando nos tratamentos de 0 (controle), 60 e 120g/cavalo/dia de linhaça. Os cavalos foram suplementados por período de 30 dias. A atividade física consistiu em trabalho para salto no nível de equitação fundamental. As variáveis funcionais mensuradas foram índice de claudicação (IC), comprimento da passada e biometria da articulação metacarpofalangeana - MCF (circunferência e ângulo de flexão). Observou-se efeito significativo da suplementação com linhaça, independentemente da dosagem, sobre o IC. Ainda, o fornecimento de 120g de linhaça/cavalo/dia aumentou o comprimento da passada dos cavalos ao trote (P<0,05) e promoveu redução de 0,5cm na circunferência da articulação MCF (P<0,05) em comparação ao grupo controle. A suplementação de cavalos de salto com 120g/dia de linhaça promoveu maior comprimento da passada ao trote e redução de edema na articulação metacarpofalangeana, melhorando suas capacidades funcionais.
Functional capacity of jumping horses supplemented with linseed
Keywords: equino; ácido graxo ômega-3; articulação metacarpofalangeana; comprimento da passada; equine; joint metacarpophalangeal; omega-3 fatty acid; stride length